Doctrinaire against Witches. Material Evidence of Criminality - Torquemada Sánchez, María Jesús (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2020)
The current piece of work is based upon the texts written by judicial doctrine in between the 14th and 17th centuries with the aim to show judges judging based on witchcraft and superstitions on the evidence of substances and magic items bound to provide evidence at secular courts and inquisitorial ones based on the above mentioned behaviour.
Keywords: Judicial Doctrine; Witchcraft; Superstitions; Physical Evidence; Magic Tools